2016
DOI: 10.1002/stem.2287
|View full text |Cite
|
Sign up to set email alerts
|

Histone Chaperone SSRP1 is Essential for Wnt Signaling Pathway Activity During Osteoblast Differentiation

Abstract: Cellular differentiation is accompanied by dramatic changes in chromatin structure which direct the activation of lineage-specific transcriptional programs. Structure-specific recognition protein-1 (SSRP1) is a histone chaperone which is important for chromatin-associated processes such as transcription, DNA replication and repair. Since the function of SSRP1 during cell differentiation remains unclear, we investigated its potential role in controlling lineage determination. Depletion of SSRP1 in human mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…38 Furthermore, it has been reported that SSRP1 is involved in canonical Wnt/β-catenin-mediated signalling pathways. 11 The activation of the Wnt/β-catenin signalling pathway also plays a key role in the formation of CRC; mutations in the negative regulatory components of APC occur in more than 90% of colorectal tumours. 39 We have been suggested that the high expression levels of SSRP1 regulate the Wnt/β-catenin pathways in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Furthermore, it has been reported that SSRP1 is involved in canonical Wnt/β-catenin-mediated signalling pathways. 11 The activation of the Wnt/β-catenin signalling pathway also plays a key role in the formation of CRC; mutations in the negative regulatory components of APC occur in more than 90% of colorectal tumours. 39 We have been suggested that the high expression levels of SSRP1 regulate the Wnt/β-catenin pathways in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…10 SSRP1 is highly expressed in the early stages of embryonic development, and its expression is reduced gradually in the organs as birth nears and postnatal life begins, which suggests that SSRP1 plays a role in maintaining the undifferentiated cell state. [10][11][12] Moreover, SSRP1 is upregulated in various tumours, such as breast cancer and ovarian cancer, and is associated with a worse prognosis. [13][14][15] RNA interference (RNAi) knocks down SSRP1, inhibits tumour transformation and impairs tumour cell viability, but nontumour cells can tolerate this knockdown well.…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by in vitro induced differentiation experiments [22]. Several studies from other labs also showed that FACT is involved in the early steps of differentiation [23, 24], suggesting a role in actively proliferating progenitors of differentiated cells, the most probable source of cancer stem cells. Based on these findings, FACT elevation in multiple tumors, including BrCa [25] and ovarian cancer [26] was less surprising and more biologically explicable, though the mechanism by which FACT facilitates tumor growth is still obscure.…”
Section: Introductionmentioning
confidence: 67%
“…For luciferase assays, the Dual-Luciferase Reporter Assay System (Promega) was used as previously described (29). Briefly, cells were co-transfected with a SNAI2 -promoter containing luciferase promoter construct (kindly provided by S. Hüttelmaier; (30) together with a plasmid expressing Renilla luciferase (pRL-TK, Promega) and either an empty control vector (pSG5) or KLF10 expression vector.…”
Section: Methodsmentioning
confidence: 99%